ORNAMENTATIONS OF PERFORMANCE OF CERTAIN MUSICAL INSTRUMENTS (Spectrum Journal of Innovation, Reforms and Development, 2022)
In this article, we will talk about the development of the playing skills of the melody, the development of the Clavier art, difficult strings, Singaporean, mordent, Triol, melism, Trell.